(3EOGQI GdhbJ (B:s (3GdfXQjI hGdJWHjb (B/s - (3YdjGf, QHMj eUWais ((3YeGf(B: s (3OGQ LQjQ ddfTQ hGdJhRjY(B, s, 2005)
(3GdhbJ hEOGQI GdhbJ(B:(3eaGgje CSGSjI,JNWjW GdhbJ,EOGQI GdhbJ hJhRjYg,JfXje GdhbJ hJSLjdg,eVjYGJ GdhbJ,GSJZdGd GdhbJ hEOGQI eVjYGJg,EOGQI GdGLJeGYGJ,GdJcfhdhLjG hEOGQI GdhbJ,JhUjGJ YGeI dEOGQI GdhbJs
(3HHdjhZQGajG(B:(3U(B.303s
Keywords: (3EOGQIs; (3GdJhbjJs